Enhancing Outcomes for Struggling Readers: Empirical Analysis of The Fluency Development Lesson. Issue 1 (2nd January 2019) - Zimmerman, Belinda S.; Rasinski, Timothy V.; Was, Christopher A.; Rawson, Katherine A.; Dunlosky, John; Kruse, Sharon D.; Nikbakht, Elham
Abstract : This study investigated the efficacy of the Fluency Development Lesson (FDL) in improving reading achievement in primary grade struggling readers. 30 readers, enrolled in a summer reading clinic, participated in daily 40-min mini-reading lessons across 5 weeks. During the fluency lessons, readers practiced and developed their literacy skills through participation in repeated readings, word work, rehearsal, and performance. Assessments measured comprehension, reading fluency, including word recognition accuracy, reading speed, and prosody. Control students also took the pre- and post-intervention tests; their performance did not change with repeated testing. The Fluency Development Lesson students showed significant gains on all measures.